2020
DOI: 10.1182/bloodadvances.2020002081
|View full text |Cite|
|
Sign up to set email alerts
|

The spectrum and severity of bleeding in adolescents with low von Willebrand factor–associated heavy menstrual bleeding

Abstract: Low von Willebrand factor (VWF) in adults is associated with significant bleeding, most notably heavy menstrual bleeding (HMB) and postpartum hemorrhage, although this has not been characterized in adolescents. The objectives of this analysis of a multicenter single arm observational cohort study in adolescents with low VWF–associated HMB were to describe the bleeding phenotype, HMB severity, and related complications. Eligibility criteria included postmenarchal females <21 years of age with HMB (Pictor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(48 citation statements)
references
References 29 publications
1
47
0
Order By: Relevance
“…Finally, it is clear that there is a subgroup of patients with VWF levels in the 30 to 50 IU/dL who do bleed significantly despite their mild reductions in plasma VWF levels. 19,21,46,47 Importantly, the bleeding tendency in these low VWF patients does not correlate with VWF levels and thus is likely multifactorial in etiology. 16 Individuals with low VWF, particularly those with high BAT scores, certainly require perioperative hemostatic treatment.…”
Section: Interindividual Variability In Bleeding Phenotypementioning
confidence: 92%
See 2 more Smart Citations
“…Finally, it is clear that there is a subgroup of patients with VWF levels in the 30 to 50 IU/dL who do bleed significantly despite their mild reductions in plasma VWF levels. 19,21,46,47 Importantly, the bleeding tendency in these low VWF patients does not correlate with VWF levels and thus is likely multifactorial in etiology. 16 Individuals with low VWF, particularly those with high BAT scores, certainly require perioperative hemostatic treatment.…”
Section: Interindividual Variability In Bleeding Phenotypementioning
confidence: 92%
“…44,45 Interestingly, several recent independent studies have demonstrated that some individuals with mild reductions in plasma VWF levels do have significantly increased bleeding assessment tool (BAT) scores. 19,21,46,47 In particular, some women with VWF in the 30 to 50 IU/dL range have subjective and objective evidence of abnormal heavy menstrual bleeding and postpartum hemorrhage (PPH). 46,47 In these patients, bleeding severity is not correlated with plasma VWF levels and pathological VWF sequence variants are less common.…”
Section: Low Vwfmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8][9][10] Importantly, from a clinical perspective, these studies have demonstrated that a significant number of patients with plasma VWF:Ag in the 30-50 IU/dl range have a bleeding phenotype. [5][6][7][10][11][12] In particular, significantly increased heavy menstrual bleeding and postpartum hemorrhage have been reported in some women with low VWF. 5,10 Despite its prevalence and associated morbidity, the biological mechanisms responsible for the reduced plasma VWF:Ag in patients with low VWF remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][10][11][12] In particular, significantly increased heavy menstrual bleeding and postpartum hemorrhage have been reported in some women with low VWF. 5,10 Despite its prevalence and associated morbidity, the biological mechanisms responsible for the reduced plasma VWF:Ag in patients with low VWF remain unclear. 4 However, they have been shown to be inherited independent of the VWF gene on chromosome 12 in some families.…”
Section: Introductionmentioning
confidence: 99%